FIVE BENEFITS OF TEACHING WITH EDUCATIONAL GAMES (International Conference on Medical Science, Medicine and Public Health, 2025)
In recent years, the integration of educational games into the learning environment has gained widespread recognition as a dynamic teaching strategy. This research article explores the major benefits of incorporating educational games into instruction, highlighting how they enhance student engagement, motivation, knowledge retention, collaborative skills, and problem-solving abilities. Drawing from contemporary studies and classroom observations, this paper aims to present a compelling case for the systematic use of educational games in modern education.